Paciente de sexo femenino de 40 años de edad con sobrepeso y dislipidemia mixta. - Vaca Navarrete, Lorrayne Angeline (2020)
Metabolic diseases are generally caused by unhealthy behaviors and lifestyles, which lead to metabolic disorders such as obesity, lipid and carbohydrate disorders. Dyslipidemia or hyperlipidemia, in a health problem related to the metabolism of fats, these are produced by an elevation of total cholesterol greater than 200mg / dl and triglycerides greater than 150 mg / dl; Currently, this problem is considered a risk factor for atherosclerosis that increases the morbidity rate from cardiovascular diseases worldwide; Obesity is a health problem that affects billions of people of different ethnic groups and ages, weight gain is related to poor eating habits in the population. The present clinical case study refers to a 40-year-old female woman with a history of polycystic syndrome and overweight; He refers that two years ago, through a check-up, they detected high levels of cholesterol and triglycerides; He mentions that in the last few days nausea, vomiting, headache have occurred, which is why I seek medical attention; On normal physical examination without incident; The nutritional assessment reflected an overweight BMI 26.9kg / m2 with increased cardiovascular risk evidenced with a waist circumference of 97 cm. His biochemical tests indicated hypertriglyceridemia, hypercholesterolemia and elevated LDL and decreased HDL; After collecting all the data, the patient is diagnosed with Mixed Dyslipidemia, for which she is sent to the nutrition service for intervention and nutritional treatment; An individualized dietary plan was made that was adjusted to the problems present in the patient, a feeding model was prescribed following the guidelines of the Mediterranean diet, which was divided into 4 meal times; A monthly follow-up and monitoring will be carried out, analyzing anthropometric, biochemical, clinical and dietary data to check if the nutritional intervention had results.